Automated Processing of Mechanical Test Data for Various Composite Materials Using MATLAB - Vasile BRIA; Marius BODOR (The Annals of “Dunarea de Jos” University of Galati. Fascicle IX, Metallurgy and Materials Science, 2025)
The behaviour of composite materials during the mechanical testing process might exhibit, in some situations, very different patterns compared to those of conventional materials. This is why the eventual automation of data processing might require additional steps towards obtaining realistic results from mechanical testing. The present work addresses this issue by proposing an algorithm written using MATLAB software and applying it in processing data from mechanical testing of selected composite materials with various compositions and behaviours.